2000
DOI: 10.1046/j.1365-2036.2000.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose ecabet sodium improves the eradication rate of Helicobacter pylori in dual therapy with lansoprazole and amoxicillin

Abstract: Aim: The additive effect of ecabet sodium in combination with dual therapy on Helicobacter pylori eradication was evaluated. Methods: H. pylori‐positive chronic gastritis patients were randomly assigned to one of the following three groups and medicated for 2 weeks. Group LA: dual therapy (lansoprazole 30 mg o.d. plus amoxicillin 750 mg b.d.). Group LA1E: dual therapy plus ecabet sodium (1 g b.d.). Group LA2E: dual therapy plus ecabet sodium (2 g b.d.). Patients were evaluated 4 weeks after the cessation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Ecabet improves the efficacy of antibiotic therapy for H. pylori-infected patients with peptic ulcer (1,16) and has been suggested to exert unknown anti-H. pylori actions besides inhibition of urease activity (1,16). In this study, we found that ecabet inhibited the H. pylori LPStriggered expression of both Nox1 and Noxo1 mRNAs in the 10% FBS-containing medium, resulting in complete inhibition of the priming effect of H. pylori LPS (Fig.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Ecabet improves the efficacy of antibiotic therapy for H. pylori-infected patients with peptic ulcer (1,16) and has been suggested to exert unknown anti-H. pylori actions besides inhibition of urease activity (1,16). In this study, we found that ecabet inhibited the H. pylori LPStriggered expression of both Nox1 and Noxo1 mRNAs in the 10% FBS-containing medium, resulting in complete inhibition of the priming effect of H. pylori LPS (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…Cells treated with 20 mg/ml ecabet or with 20 mg/ml ecabet plus 20 EU/ml H. pylori LPS, respectively, released 2.66 Ϯ 0.71 (n ϭ 4) or 2.42 Ϯ 0.36% (n ϭ 4) of the activity during the same period. Thus the concentrations used in this study were not toxic and may be clinically relevant, because patients are usually taking ecabet 1 (1) or 2 g twice a day (16).…”
Section: Effects Of Ecabet On H Pylori Lps-induced Upregulation Of Omentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have demonstrated that ecabet sodium used with any of several regimens increases the eradication rate of H. pylori infection: Ohkusa et al (22) reported that ecabet sodium increased the eradication rates of dual therapy with lansoprazole and amoxicillin from 58% to 78%; Kagaya et al (23) reported that this agent increased the eradication rate by dual lansoprazole/amoxicillin therapy from 43% to 79%; and Kim et al (24) reported that it increased the eradication rate with triple PPI/amoxicillin/clarithromycin therapy from 78.8% to 88.6%. In the present study, therefore, we examined the eradication rates of ecabet sodiumbased regimens, such as LAC2E for 1 week and LA2E for 2 weeks, in comparison with LAC for 1 week in patients in whom eradication of H. pylori with the triple PPI/amoxicillin/clarithromycin therapy had failed.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have documented the effects of ES on peptic ulcers [13] as well as ulcerative colitis [14]. ES has an antibacterial effect on Helicobacter pylori and accelerates the eradication rate of Helicobacter pylori in vivo [15][16][17]. Lee et al [18] reported the effects of ES in FD patients in a prospective, double-blinded, randomized trial.…”
Section: Introductionmentioning
confidence: 96%